Japan’s Muslim-Friendly Tourism in The View of Maqasid Sharia Dharuriyah - Srifauzi, Aulia; Surwandono, Surwandono (UNIDA Gontor, 2023)
Japan is a Muslim minority country but intensively promotes halal or Muslim-friendly tourism with the slogan